Occasional Interventions to Target Rates - Karen K. Lewis (American Economic Review, 1995)
This paper develops a model of central-bank intervention based upon a policy characteristic of foreign-exchange interventions by the United States, Germany, and Japan in the late 1980's and evaluates it empirically. Central bankers intervene with greater intensity as rates deviate from target levels, but they also try to stabilize rates around current levels. The model is estimated using exchange rates and data based upon observed central-bank interventions. Interestingly, the estimates of the model are consistent with the predictions of the theoretical model for both the deutsche-mark/dollar rate and, less strongly, for the yen/dollar rate.